Multidisciplinary Research and Practice for Information Systems IFIP WG 8.4, 8.9/TC 5 International Cross-Domain Conference and Workshop on Availability, Reliability, and Security, CD-ARES 2012, Prague, Czech Republic, August 20-24, 2012. Proceedings - Quirchmayr, Gerald; Basl, Josef; You, Ilsun; Xu, Lida.; Weippl, Edgar; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the IFIP WG 8.4, 8.9, TC 5 International Cross Domain Conference and Workshop on Availability, Reliability and Security, CD-ARES 2012, held in Prague, Czech Republic, in August 2012. The 50 revised papers presented were carefully reviewed and selected for inclusion in the volume. The papers concentrate on the many aspects of information systems bridging the gap between research results in computer science and the many application fields. They are organized in the following topical sections: cross-domain applications: aspects of modeling and validation; trust,security, privacy, and safety; mobile applications; data processing and management; retrieval and complex query processing; e-commerce; and papers from the colocated International Workshop on Security and Cognitive Informatics for Homeland Defense, SeCIHD 2012.
Cross-Domain Applications: Aspects of Modeling and Validation -- Trust, Security, Privacy and Safety -- Mobile Applications -- Data Processing and Management -- Retrieval and Complex Query Processing -- E-Commerce -- International Workshop on Security and Cognitive Informatics for Homeland Defense (SeCIHD).
Keywords: Computer science; Data protection; Data encryption (Computer science).; Information storage and retrieval systems; Management information systems; Computer Science; Information Systems Applications (incl. Internet).; Systems and Data Security; Information Storage and Retrieval; Data Encryption; e-Commerce/e-business.; Business Information Systems